Lithium adsorption material and preparation method and application thereof
By connecting the amino-modified lithium ion sieve with the cyclodextrin-polyurethane polymer framework through chemical bonds, the problem of lithium adsorption materials being easily shedded and not resistant to acid and alkali during long-term use is solved, and high adsorption capacity and magnesium lithium selection are achieved and improves the stability and service life of the material.
Patent Information
- Application Number
- CN202311048391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
Existing lithium adsorbent materials are prone to fall off during long-term use and are not resistant to strong acids and alkalis, resulting in a degradation of adsorption performance.
The lithium-ion sieve modified with amino group is connected to the cyclodextrin-polyurethane polymer framework through chemical bonds. The lithium adsorption material formed has a high pore structure and a stable framework, which can adsorb lithium under alkaline conditions and desorption under acid conditions.
It significantly improves the adsorption capacity and magnesium lithium selectivity of lithium adsorbent materials, reduces the damage to the material structure by acid and alkali, and extends the service life of the material.
Smart Images

Figure CN119488886A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion adsorption materials, and in particular to a lithium adsorption material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the lithium battery industry, the demand for lithium resources in all walks of life is continuing to grow, and the importance of lithium production is also increasing. At present, lithium resources are mainly distributed in lithium ore and salt lake brine, but lithium ore resources are constantly decreasing and the development cost is increasing; in contrast, the lithium water resources in salt lake brine are low in cost and abundant in reserves. China is the largest lithium consumer country. Although it has abundant liquid lithium resources, extracting lithium from lithium water resources is a challenging task, so most upstream lithium source materials still rely on imports. The main methods for extracting lithium from salt lakes in China include adsorption, precipitation, extraction, electrodialysis, calcination, etc. Among them, the adsorption method has the advantages of simple process, green energy saving, and good selectivity. It is superior to other methods in terms of time and cost, and has broad application prospects. Since domestic salt lake brine generally has the problems of low lithium taste and high magnesium-lithium ratio, the core of lithium extraction by adsorption is to prepare an adsorbent with high adsorption capacity and high lithium-magnesium separation performance. Secondly, it is necessary to granulate the adsorbent powder to overcome the problem of powder loss during use. Due to their special structure, manganese and titanium lithium ion sieve powder adsorbents have the best selective adsorption effect on lithium ions under alkaline conditions and the best desorption effect on lithium ions under acidic conditions. Therefore, the adsorbent particles prepared by granulation need to be acid and alkali resistant. Common granulation methods include natural polymers such as sodium alginate and synthetic resins such as polyvinyl chloride. The adsorbent particles obtained by granulation methods such as sodium alginate are not resistant to acid and alkali. Although polyvinyl chloride is resistant to acid and alkali, it has poor hydrophilicity. Therefore, it is urgent to develop an adsorbent granulation product with high adsorption capacity, high magnesium-lithium selectivity and acid and alkali resistance.
[0003] CN114011386A discloses a method for preparing lithium adsorption particles, wherein LiCl·2Al(OH)3·nH2O powder is mixed with polyol, diisocyanate, etc. to obtain a polyurethane-based granulated adsorbent, which is then further mixed with a binder for granulation, and the solvent is removed to obtain lithium adsorption particles. However, this method has complicated steps, requires secondary granulation, and has a low adsorption capacity. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of lithium ion sieves in the prior art that are easy to fall off and are not resistant to strong acids and alkalis, and to provide a lithium adsorption material and a preparation method and application thereof. The lithium adsorption material comprises a skeleton and an amino-modified lithium ion sieve dispersed in the skeleton. The lithium ion sieve is connected to the skeleton by chemical bonds, so that the lithium ion sieve is not easy to fall off during long-term use. The skeleton is loose, so that the lithium adsorption material has a large pore structure, thereby significantly improving the adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material.
[0005] In order to achieve the above object, the first aspect of the present invention provides a lithium adsorption material, wherein the lithium adsorption material comprises a skeleton and an amino-modified lithium ion sieve dispersed in the skeleton;
[0006] The lithium ion sieve is connected to the framework via the structure shown in Formula I;
[0007]
[0008] The skeleton includes structural unit A, structural unit B, structural unit C and structural unit D;
[0009] The structural unit A and the structural unit C are connected by the structure shown in formula II;
[0010]
[0011] The structural unit B and the structural unit C are connected by the structure shown in formula III;
[0012]
[0013] The structural unit C and the structural unit D form a structure shown in Formula IV;
[0014]
[0015] Ar1 is the residue after dehydroxylation of polyol; Ar2 is the residue after dehydroxylation of polyisocyanate; Ar3 is the residue after dehydroxylation of cyclodextrin;
[0016] R1 is a C3-C6 alkylene group.
[0017] A second aspect of the present invention provides a method for preparing a lithium adsorption material, wherein the preparation method comprises the following steps:
[0018] S1, performing amino modification on the lithium ion sieve to obtain an amino-modified lithium ion sieve;
[0019] S2, mixing the amino-modified lithium ion sieve, the polyol, the cyclodextrin and the chain extender in water to obtain a mixed solution A;
[0020] S3. Under stirring conditions, an organic solution containing polyisocyanate is added dropwise to mixed solution A to obtain mixed solution B. After the reaction, the product after the reaction is heat-treated to obtain a semi-solidified cross-linked product. After drying and crushing, a lithium adsorption material is obtained.
[0021] The third aspect of the present invention provides a lithium adsorption material obtained by the above preparation method.
[0022] A fourth aspect of the present invention provides an application of the above-mentioned lithium adsorption material in extracting lithium from salt lakes.
[0023] Through the above technical scheme, the lithium adsorption material and the preparation method and application thereof provided by the present invention have the following beneficial effects.
[0024] The lithium adsorption material of the present invention has a cyclodextrin-polyurethane polymer skeleton including structural units A, B, C and D, and the amino-modified lithium ion sieve is dispersed in the polymer skeleton in a bonded form, so that the lithium ion sieve is not easy to fall off.
[0025] In LiCl solution, Li + It exists in hydration, and the hydrated structure is usually [Li2Cl(H2O) 4-6 ]0.Li + Hydrated ion radius When lithium adsorption materials adsorb ions, they need to overcome the hydration energy of the ions, which increases the energy barrier of adsorption. The inventors found that the amide bond -CO-NH- and Li + The electrostatic effect can overcome the free energy of lithium ion complexation reaction and destroy the Li + The first water layer makes Li + In the form of naked ions, Li + Rapidly enter the internal pores of the ion sieve or cyclodextrin, thereby accelerating the rate of the adsorption reaction.
[0026] Furthermore, structural unit B carries the residue of cyclodextrin after dehydroxylation. Since the size of the cyclodextrin cavity matches that of lithium ions, the lithium adsorption material can specifically adsorb lithium ions and synergize with the amino-modified lithium ion sieve to significantly improve the adsorption capacity and selectivity of the lithium adsorption material for lithium ions.
[0027] Furthermore, due to the stability of the polyurethane skeleton structure and the bonding effect between the lithium ion sieve and the skeleton, the lithium adsorption material provided by the present invention can adsorb lithium under alkaline conditions and desorb lithium under acidic conditions, thereby reducing the damage of acid and alkali to the structure of the lithium adsorption material.
[0028] In the preparation method of the lithium ion sieve provided by the present invention, a cyclodextrin-polyurethane polymer skeleton is formed by in-situ polymerization reaction of an amino-modified lithium ion sieve, cyclodextrin, polyol, polyisocyanate and a chain extender, and the amino-modified lithium ion sieve is connected to the skeleton by chemical bonds, thereby avoiding the traditional technology of directly physically mixing the lithium ion sieve with the polyurethane for granulation, which leads to a decrease in the performance of the lithium adsorption material due to the shedding of the lithium ion sieve during long-term use. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 3 is a scanning electron microscope image of the lithium adsorption material prepared in Example 1.
[0030] Figure 2 This is a scanning electron microscope image of the lithium adsorption material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0031] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0032] A first aspect of the present invention provides a lithium adsorption material, wherein the lithium adsorption material comprises a skeleton and an amino-modified lithium ion sieve dispersed in the skeleton;
[0033] The lithium ion sieve is connected to the framework via the structure shown in Formula I;
[0034]
[0035] The skeleton includes structural unit A, structural unit B, structural unit C and structural unit D;
[0036] The structural unit A and the structural unit C are connected by the structure shown in formula II;
[0037]
[0038] The structural unit B and the structural unit C are connected by the structure shown in formula III;
[0039]
[0040] The structure unit C and the structure unit D form a structure shown in Formula IV;
[0041]
[0042] Ar1 is the residue after dehydroxylation of polyol; Ar2 is the residue after dehydroxylation of polyisocyanate; Ar3 is the residue after dehydroxylation of cyclodextrin;
[0043] R1 is a C3-C6 alkylene group.
[0044] The lithium adsorption material of the present invention has a cyclodextrin-polyurethane polymer skeleton including structural units A, B, C and D, and the amino-modified lithium ion sieve is dispersed in the polymer skeleton in a bonded form, so that the lithium ion sieve is not easy to fall off, and the amide bond -CO-NH- and Li + The electrostatic effect can overcome the free energy of lithium ion complexation reaction and destroy Li + The first water layer makes Li + In the form of naked ions, Li + Rapidly enter the internal pores of the ion sieve or cyclodextrin, thereby accelerating the rate of the adsorption reaction.
[0045] Furthermore, structural unit B carries the residue of cyclodextrin after dehydroxylation. Since the size of the cyclodextrin cavity matches that of lithium ions, the lithium adsorption material can specifically adsorb lithium ions and synergize with the amino-modified lithium ion sieve to significantly improve the adsorption capacity and selectivity of the lithium adsorption material for lithium ions.
[0046] Furthermore, the polyurethane skeleton structure in the lithium adsorption material provided by the present invention is stable and the lithium ion sieve has a bonding effect with the skeleton, so that the lithium adsorption material can adsorb lithium under alkaline conditions and desorb under acidic conditions, thereby reducing the damage of acid and alkali to the lithium adsorption material.
[0047] According to the present invention, the polyol is selected from at least one of polyethylene glycol, polypropylene glycol and polyether polyol.
[0048] In the present invention, when the above-mentioned polyol is used, the lithium adsorption material has a macroporous structure, thereby improving the adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material.
[0049] Furthermore, the polyol is polyethylene glycol.
[0050] According to the present invention, the weight average molecular weight of the polyol is 200-2000 g / mol.
[0051] Furthermore, the weight average molecular weight of the polyol is 800-1000 g / mol.
[0052] In the present invention, when the weight average molecular weight of the polyol is within the range required by the present invention, the formed polyurethane skeleton is loose and porous, thereby improving the adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material.
[0053] According to the present invention, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.
[0054] In the present invention, the cavities of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin are more closely matched to the sizes of lithium ions, so that the lithium adsorption material can specifically adsorb lithium ions, thereby improving the adsorption capacity of the lithium adsorption material for lithium in the solution and the magnesium-lithium separation coefficient.
[0055] Furthermore, the cyclodextrin is β-cyclodextrin.
[0056] According to the present invention, Ar2 is selected from at least one of the following groups:
[0057]
[0058] Wherein, R2 and R3 are each independently a methylene group, and R4 is a C6-C9 straight chain alkylene group or a branched chain alkylene group.
[0059] In the present invention, when Ar2 has the above-mentioned specific structure, the polyurethane skeleton is more stable.
[0060] According to a preferred embodiment of the present invention, Ar2 in the skeleton comprises Preferably, based on the total weight of the structural unit C, it comprises The content of the structural unit C is 50wt%-75wt%. The content range is calculated by the weight of the raw material input corresponding to each Ar2.
[0061] In the present invention, when Ar2 is the above-mentioned specific combination, the obtained lithium adsorption material has a stable skeleton structure.
[0062] According to the present invention, based on the total weight of the lithium adsorption material, the content of the amino-modified lithium ion sieve is 38wt%-75wt%, the content of the structural unit A is 10wt%-30wt%, the content of the structural unit B is 3wt%-16wt%, the content of the structural unit C is 6wt%-23wt%, and the content of the structural unit D is 0.3wt%-9wt%;
[0063] In the present invention, when the content of each structure in the skeleton meets the requirements of the present invention, the obtained adsorption material can take into account the stability of the main body and has high adsorption capacity and selectivity.
[0064] In the present invention, the saturated adsorption capacity of the lithium adsorbent material is directly related to the amino-modified lithium ion sieve in the lithium adsorbent material. It can be understood that the saturated adsorption capacities are comparable only when the content of the amino-modified lithium ion sieve is the same.
[0065] Furthermore, based on the total weight of the lithium adsorption material, the content of the amino-modified lithium ion sieve is 45wt%-70wt%, the content of the structural unit A is 13wt%-23wt%, the content of the structural unit B is 6wt%-9wt%, the content of the structural unit C is 8wt%-20wt%, and the content of the structural unit D is 1wt%-7wt%.
[0066] According to the present invention, the amino-modified lithium ion sieve is a lithium ion sieve modified by an aminosilane coupling agent.
[0067] In the present invention, the lithium ion sieve modified by the aminosilane coupling agent can be better bonded in the polymer skeleton and is not easy to fall off, so that the lithium adsorption material has a high lithium ion adsorption capacity and magnesium-lithium selectivity.
[0068] According to the present invention, based on the total weight of the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is 0.1 wt%-2 wt%.
[0069] Furthermore, based on the total weight of the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is 0.5wt%-1.8wt%.
[0070] According to the present invention, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.
[0071] According to the present invention, the lithium ion sieve is a titanium-based lithium ion sieve.
[0072] Furthermore, the lithium ions are selected from Li2TiO3, Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of .
[0073] According to the present invention, the average particle size of the lithium ion sieve is 0.01-500 μm.
[0074] In the present invention, when the average particle size of the lithium ion sieve meets the requirements of the present invention, the amino-modified lithium ion sieve can better perform bonding reaction, so that the lithium ion sieve is not easy to fall off from the skeleton.
[0075] Furthermore, the average particle size of the lithium ion sieve is 0.03-300 μm.
[0076] According to the present invention, the specific surface area of the lithium adsorption material is 8-500m 2 / g.
[0077] According to the present invention, the pore size of the lithium adsorption material is 0.1-10 microns.
[0078] According to the present invention, the pore volume of the lithium adsorption material is 10-100m 3 / g.
[0079] According to the present invention, the average particle size of the lithium adsorption material is 0.01-3 mm.
[0080] In the present invention, when at least one of the average particle size, specific surface area, pore size, and pore volume of the lithium adsorption material meets the above characteristics, it is beneficial to improve the adsorption capacity, magnesium-lithium selectivity, and adsorption rate of the lithium adsorption material.
[0081] Furthermore, the specific surface area of the lithium adsorption material is 10-30m 2 / g.
[0082] Furthermore, the pore size of the lithium adsorption material is 2-5 microns.
[0083] Furthermore, the pore volume of the lithium adsorption material is 40-60m 3 / g.
[0084] Furthermore, the average particle size of the lithium adsorption material is 1-3 mm.
[0085] A second aspect of the present invention provides a method for preparing a lithium adsorption material, wherein the preparation method comprises the following steps:
[0086] S1, performing amino modification on the lithium ion sieve to obtain an amino-modified lithium ion sieve;
[0087] S2, mixing the amino-modified lithium ion sieve, the polyol, the cyclodextrin and the chain extender in water to obtain a mixed solution A;
[0088] S3. Under stirring conditions, an organic solution containing polyisocyanate is added dropwise to mixed solution A to obtain mixed solution B. After the reaction, the product after the reaction is heat-treated to obtain a semi-solidified cross-linked product. After drying and crushing, a lithium adsorption material is obtained.
[0089] In the preparation method of the lithium ion sieve provided by the present invention, a cyclodextrin-polyurethane polymer skeleton is formed by in-situ polymerization reaction of an amino-modified lithium ion sieve, cyclodextrin, polyol, polyisocyanate and a chain extender, and the amino-modified lithium ion sieve is connected to the skeleton by chemical bonds, thereby avoiding the traditional technology of directly physically mixing the lithium ion sieve with the polyurethane for granulation, which leads to a decrease in the performance of the lithium adsorption material due to the shedding of the lithium ion sieve during long-term use.
[0090] According to the present invention, in step S1, the lithium ion sieve is a titanium-based lithium ion sieve.
[0091] Furthermore, the lithium ions are selected from Li2TiO3, Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of .
[0092] According to the present invention, the average particle size of the lithium ion sieve is 0.01-500 μm
[0093] Furthermore, the average particle size of the lithium ion sieve is 0.03-300 μm
[0094] According to the present invention, the lithium ion sieve is modified by amino silane coupling agent.
[0095] In the present invention, aminosilane coupling agent is used for modification, so that the lithium ion sieve can be better bonded to the polymer skeleton and is not easy to fall off. The obtained lithium adsorption material has high lithium ion adsorption capacity and magnesium-lithium selectivity.
[0096] Further, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.
[0097] According to the present invention, the mass ratio of the lithium ion sieve to the aminosilane coupling agent is 1:0.5-2.
[0098] Furthermore, the mass ratio of the lithium ion sieve to the aminosilane coupling agent is 1:0.5-1.8.
[0099] According to the present invention, the conditions for the amino modification include: pH value of 1-3, reaction temperature of 40-95° C., and reaction time of 0.5-12 h.
[0100] According to the present invention, in step S3, based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve is 38wt%-75wt%, the content of the polyol is 10wt%-30wt%, the content of the cyclodextrin is 3wt%-16wt%, the content of the chain extender is 0.3wt%-9wt%, and the content of the polyisocyanate is 6wt%-23wt%.
[0101] In the present invention, when the content of each component meets the above-mentioned limitations, the skeleton structure of the polyurethane after polymerization is stable and the lithium ion sieve has a bonding effect with the skeleton, so that the lithium adsorption material can adsorb lithium under alkaline conditions and desorb under acidic conditions, thereby reducing the damage of acid and alkali to the skeleton structure of the lithium adsorption material.
[0102] Furthermore, based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve is 45wt%-70wt%, the content of the polyol is 13wt%-23wt%, the content of the cyclodextrin is 6wt%-9wt%, the content of the chain extender is 1wt%-7wt%, and the content of the polyisocyanate is 8wt%-20wt%.
[0103] According to the present invention, the polyol is at least one selected from polyethylene glycol, polypropylene glycol and polyether polyol.
[0104] In the present invention, when the above-mentioned polyol is selected, the obtained lithium adsorption material has a macroporous structure, thereby improving the adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material.
[0105] Furthermore, the polyol is polyethylene glycol.
[0106] According to the present invention, the weight average molecular weight of the polyol is 200-2000 g / mol.
[0107] Furthermore, the weight average molecular weight of the polyol is 800-1000 g / mol.
[0108] In the present invention, when the weight average molecular weight of the polyol is within the range required by the present invention, the formed polyurethane skeleton is loose and porous, thereby improving the adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material.
[0109] According to the present invention, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.
[0110] In the present invention, the cavities of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin are more closely matched to the sizes of lithium ions, so that the lithium adsorption material can specifically adsorb lithium ions, thereby improving the adsorption capacity of the lithium adsorption material for lithium in the solution and the magnesium-lithium separation coefficient.
[0111] Furthermore, the cyclodextrin is β-cyclodextrin.
[0112] According to the present invention, the chain extender is 1,4-butanediol and / or 1,3-propylene glycol.
[0113] According to the present invention, the polyisocyanate is selected from at least one of meta-xylylene diisocyanate, hexamethylene diisocyanate, 1,4-phenylene diisocyanate, 1,3-phenylene diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate and trimethylhexamethylene diisocyanate.
[0114] According to a preferred embodiment of the present invention, the polyisocyanate is a combination of 1,4-phenylene diisocyanate and 1,3-phenylene diisocyanate. Preferably, the mass ratio of 1,4-phenylene diisocyanate to 1,3-phenylene diisocyanate is 1:3-1.
[0115] In the present invention, when the above-mentioned combination of polyisocyanates is used, the polyurethane skeleton structure of the prepared lithium adsorption material is made more stable, and the damage of acid and alkali to the structure of the lithium adsorption material is reduced.
[0116] In the present invention, in step S3, the content of polyisocyanate in the polyisocyanate-containing organic solution is 3wt%-10wt%. There is no particular limitation on the type of organic solvent, and conventional organic solvents in the art can be used, such as one or more of n-hexane, dodecane, n-heptane, and alkane solvent oils (Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).
[0117] Furthermore, the content of polyisocyanate in the polyisocyanate-containing organic solution is 4wt%-6wt%.
[0118] According to the present invention, the reaction conditions include: reaction temperature of 30-70° C., and reaction time of 5-100 min.
[0119] In the present invention, when the above reaction conditions are adopted, it is more conducive to the in-situ polymerization reaction between the components to form a cyclodextrin-polyurethane polymer skeleton, and the amide bond -CO-NH- in the polyurethane skeleton and Li + The electrostatic effect overcomes the free energy of the complexation reaction and destroys Li + The first water layer makes Li +It exists in the form of naked ions and quickly enters the internal pores of ion sieves or cyclodextrins, accelerating the rate of the adsorption reaction.
[0120] Furthermore, the reaction conditions include: reaction temperature of 40-60° C., and reaction time of 10-30 min.
[0121] According to the present invention, the heat treatment conditions include: the heat treatment temperature is 80-150° C., and the heat treatment time is 5-60 min.
[0122] Furthermore, the heat treatment conditions include: the heat treatment temperature is 85-90° C., and the heat treatment time is 10-30 min.
[0123] According to the present invention, the preparation method further comprises: eluting the lithium adsorption material with an acidic solution.
[0124] In the present invention, the lithium adsorption material is a lithium adsorption material precursor, and the lithium adsorption material is washed with an acidic solution to make the Li + and H + Exchange to activate the precursor and obtain H-type lithium ion sieve, such as Li 1.33 Mn 1.67 O4 to H 1.33 Mn 1.67 O4, the obtained H-type lithium ion sieve has a specific adsorption effect on lithium ions.
[0125] According to the present invention, the acidic solution is selected from hydrochloric acid and / or sulfuric acid.
[0126] According to the present invention, the concentration of the acidic solution is 0.01-1 mol / L.
[0127] According to the present invention, the elution time is 0.5-24h.
[0128] The third aspect of the present invention provides a lithium adsorption material obtained by the above preparation method.
[0129] A fourth aspect of the present invention provides an application of the above-mentioned lithium adsorption material in extracting lithium from salt lakes.
[0130] The lithium adsorption material of the present invention has a high adsorption capacity for lithium ions in a solution and a strong magnesium-lithium selectivity, and is resistant to strong acids and alkalis and is hydrophilic, which is beneficial to increasing the adsorption rate of lithium and can meet the demand for lithium extraction from salt lakes.
[0131] The present invention will be described in detail below through examples.
[0132] Dynamic adsorption-desorption cycle method: The lithium adsorption material (4 g) obtained in the embodiment and the comparative example is placed in a glass column for acid washing. At 30°C, 0.5 M hydrochloric acid (200 mL) is pumped in at a flow rate of 2 BV / h using a peristaltic pump for 24 hours to wash and remove lithium ions in the material. Then, the lithium adsorbent to be tested is obtained after washing with deionized water until neutral. 250 mL of magnesium-lithium mixed solution (Li + The concentration is 100ppm, Mg 2+ A mixed solution of lithium chloride and magnesium chloride with a concentration of 2000 ppm, pH = 9.5, 30°C) was adsorbed, and then 250 mL of 0.5 M hydrochloric acid was pumped in at a flow rate of 2 BV / h using a peristaltic pump for 8 hours for desorption to obtain a desorption solution, which was recorded as the first dynamic adsorption-desorption cycle.
[0133] Static adsorption-desorption cycle method: Take 0.5g of the lithium adsorption material to be tested and mix it with 40mL of lithium magnesium mixed solution (Li + The concentration is 100ppm, Mg 2+ Static adsorption was performed in a mixed solution of lithium chloride and magnesium chloride with a concentration of 2000 ppm, pH = 9.5, 30° C. After the concentration of lithium ions and magnesium ions in the lithium-magnesium mixed solution no longer changed, desorption was performed with 100 mL of 0.5 M HCl for 24 hours.
[0134] Determination of saturated adsorption capacity of lithium adsorbent material: adopt the above-mentioned static adsorption-desorption cycle method, when the static adsorption equilibrium of the lithium adsorbent material to be tested is reached, separate the lithium adsorbent material to be tested from the mixed solution, and calculate the saturated adsorption capacity Q according to the following formula.
[0135]
[0136] Wherein, Q is the saturated adsorption capacity, in mg / g, which reflects the adsorption amount of the lithium adsorbent material when the adsorption reaches equilibrium; C0 and C are the lithium ion concentrations at the initial and saturated adsorption of the lithium adsorbent material in the lithium-magnesium mixed solution, respectively, in mg / L; V is the volume of the lithium-magnesium mixed solution, in L; M is the mass of the lithium adsorbent material to be tested, in g.
[0137] 90% adsorption capacity time of lithium adsorption material: using the above static adsorption-desorption cycle method, during the adsorption process, monitor the concentration of magnesium ions and lithium ions in the lithium-magnesium mixed solution to monitor the change of adsorption capacity over time; 90% adsorption capacity time is the time required for the adsorption capacity to reach 90% of the saturated adsorption capacity. 90% adsorption capacity time can reflect the adsorption rate of lithium adsorption material. The shorter the time required, the faster the adsorption rate.
[0138] The magnesium-lithium selectivity of the lithium adsorption material: The magnesium-lithium selectivity coefficient is calculated according to the following formula using the above-mentioned static adsorption-desorption cycle method. It refers to the priority of lithium adsorption materials for A ions when adsorbing A and B ions. The larger the value, the better the selectivity for A, which reflects the selectivity of lithium adsorption materials for different ions.
[0139]
[0140]
[0141] In the above formula, C0 is the concentration of each ion in the lithium-magnesium mixed solution, mg / L; C is the ion concentration when the lithium adsorption material to be tested is saturated with adsorption, mg / L; V is the volume of the lithium-magnesium mixed solution, mL; m is the mass of the lithium adsorption material to be tested, g. K A is the lithium ion distribution coefficient, K B is the magnesium ion partition coefficient.
[0142] Cyclic stability of lithium adsorption material: After the lithium adsorption material is cycled 30 times according to the above dynamic adsorption-desorption cycle method, the percentage of adsorption capacity decrease after 30 cycles is calculated to evaluate the cyclic stability of the lithium adsorption material.
[0143] Mass loss ratio of lithium adsorption material: the weighing method is adopted, that is, the mass of the lithium adsorption material before use (i.e., the initial mass) and the mass of the lithium adsorption material after 30 dynamic adsorption-desorption cycles are weighed respectively, and the ratio of the lost mass to the initial mass is the mass loss ratio.
[0144] The morphology of the lithium adsorption materials was characterized by scanning electron microscopy (SEM, S-4800).
[0145] The concentration of magnesium ions or lithium ions was measured by ion chromatography (ICS-1100, DIONEX, America).
[0146] The specific surface area, pore size and pore volume of lithium adsorption materials are determined by the BET method. The specific method is to determine the adsorption-desorption isotherm of lithium adsorption materials for N2 at 77K (the lithium adsorption material is degassed by heating and vacuuming to remove the impurity gas adsorbed on the surface. Then it is weighed and placed in liquid nitrogen. At liquid nitrogen temperature, the nitrogen adsorption amount of the sample is measured at different pre-set pressure points to obtain the adsorption isotherm), and the BET specific surface area, pore size and pore volume are obtained by fitting.
[0147] The average particle size of the lithium adsorbent material was measured by scanning electron microscopy.
[0148] In the lithium adsorption material, the content of the amino-modified lithium ion sieve and each structural unit is calculated by the feed ratio of the raw materials corresponding to each structural unit.
[0149] In the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is determined by a weight gain method.
[0150] The raw materials in the following preparation examples, embodiments and comparative examples are all commercially available products.
[0151] Preparation Example 1
[0152] Amino-modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80°C, and 1g of γ-aminopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:1. Hydrochloric acid was used to adjust pH = 2, and stirring was continued at 80°C for 6h to obtain amino-modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Amino-modified lithium ion sieve A was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve A was 0.14wt%.
[0153] Preparation Example 2
[0154] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80℃, and 0.8g of γ-aminopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:0.8. Hydrochloric acid was used to adjust pH=2, and the mixture was stirred continuously at 80℃ for 6h to obtain a modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Amino-modified lithium ion sieve B was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve B was 0.12wt%.
[0155] Preparation Example 3
[0156] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80°C, and 1.5g of γ-aminopropyltriethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:1.5. Hydrochloric acid was used to adjust pH=2, and the mixture was stirred continuously at 80°C for 6h to obtain a modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Amino-modified lithium ion sieve C was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve C was 1.8wt%.
[0157] Preparation Example 4
[0158] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80℃, and 0.1g of γ-aminopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:0.1. Hydrochloric acid was used to adjust pH=7.5, and continuous stirring was performed at 120℃ for 12h to obtain amino-modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 4h and dried. Amino-modified lithium ion sieve D was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve D was 0.6wt%.
[0159] Preparation Example 5
[0160] Modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80°C, and 1g of mercaptopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to coupling agent was 1:1. Hydrochloric acid was used to adjust pH=2, and continuous stirring was performed at 80°C for 6h to obtain a modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Modified lithium ion sieve E was obtained, and the content of mercaptopropyltrimethoxysilane coupling agent in the modified lithium ion sieve E was 0.11wt%.
[0161] Example 1
[0162] (1) The amino-modified lithium ion sieve A is uniformly dispersed in an aqueous solution by ultrasonication, polyethylene glycol (Mw=1000 g / mol), 1,4-butanediol and β-cyclodextrin are added, and stirred for 24 hours to obtain a mixed solution A;
[0163] (2) Under mechanical stirring, the same volume of 3 wt% 1,4-phenylene diisocyanate and 1 wt% Isopar E solution of 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve was 69 wt%, the content of the polyol was 13.8 wt%, the content of the cyclodextrin was 6.9 wt%, the content of the chain extender was 1.1 wt%, and the content of the polyisocyanate was 9.2 wt%). After reacting at 50°C for 10 min, heat treatment was performed at 80°C for 10 min to obtain a semi-solidified cross-linked product, which was dried and crushed to obtain a lithium adsorption material with a particle size of 2.5 mm.
[0164] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 75wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0165] Example 2
[0166] (1) The amino-modified lithium ion sieve B is uniformly dispersed in an aqueous solution by ultrasonication, polyethylene glycol (Mw=1000 g / mol), 1,4-butanediol and β-cyclodextrin are added, and stirred for 24 hours to obtain a mixed solution A;
[0167] (2) Under mechanical stirring, the same volume of 3 wt% Isopar E solution of 1,4-phenylene diisocyanate and 3 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve was 48.2 wt%, the content of the polyol was 19.4 wt%, the content of the cyclodextrin was 6.5 wt%, the content of the chain extender was 6.5 wt%, and the content of the polyisocyanate was 19.4 wt%). After reacting at 50°C for 10 min, heat treatment at 80°C for 10 min obtained a semi-solidified cross-linked product, which was dried and crushed to obtain a lithium adsorption material with a particle size of 2.5 mm.
[0168] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0169] Example 3
[0170] (1) The amino-modified lithium ion sieve C is uniformly dispersed in an aqueous solution by ultrasonication, polyethylene glycol (Mw=1000 g / mol), 1,4-butanediol and β-cyclodextrin are added, and stirred for 24 hours to obtain a mixed solution A;
[0171] (2) Under mechanical stirring, the same volume of 3 wt% Isopar E solution of 1,4-phenylene diisocyanate and 1 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve was 55.6 wt%, the content of the polyol was 22.2 wt%, the content of the cyclodextrin was 8.3 wt%, the content of the chain extender was 2.8 wt%, and the content of the polyisocyanate was 11.1 wt%). After reacting at 50°C for 10 min, heat treatment at 80°C for 10 min obtained a semi-solidified cross-linked product, which was dried and crushed to obtain a lithium adsorption material with a particle size of 2.5 mm.
[0172] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 75wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0173] Example 4
[0174] (1) The amino-modified lithium ion sieve A is uniformly dispersed in an aqueous solution by ultrasonication, polyethylene glycol (Mw=1000 g / mol), 1,4-butanediol and β-cyclodextrin are added, and stirred for 24 hours to obtain a mixed solution A;
[0175] (2) Under mechanical stirring, the same volume of 3 wt% Isopar E solution of 1,4-phenylene diisocyanate and 2 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve was 66.1 wt%, the content of the polyol was 13.2 wt%, the content of the cyclodextrin was 8.3 wt%, the content of the chain extender was 4.1 wt%, and the content of the polyisocyanate was 8.3 wt%). After reacting at 50°C for 10 min, heat treatment at 80°C for 10 min obtained a semi-solidified cross-linked product, which was dried and crushed to obtain a lithium adsorption material with a particle size of 2.5 mm.
[0176] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 60wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0177] Example 5
[0178] (1) The amino-modified lithium ion sieve A is uniformly dispersed in an aqueous solution by ultrasonication, polyethylene glycol (Mw=1000 g / mol), 1,4-butanediol and β-cyclodextrin are added, and stirred for 24 hours to obtain a mixed solution A;
[0179] (2) Under mechanical stirring, the same volume of 3 wt% Isopar E solution of 1,4-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve was 38.3 wt%, the content of the polyol was 23 wt%, the content of the cyclodextrin was 15.3 wt%, the content of the chain extender was 0.4 wt%, and the content of the polyisocyanate was 23 wt%). After reacting at 50°C for 10 min, heat treatment at 80°C for 10 min obtained a semi-solidified cross-linked product, which was dried and crushed to obtain a lithium adsorption material with a particle size of 2.5 mm.
[0180] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Ar3 is the residue after dehydroxylation of β-cyclodextrin; R1 is a C4 alkylene group.
[0181] Example 6
[0182] (1) The amino-modified lithium ion sieve A is uniformly dispersed in an aqueous solution by ultrasonication, polyethylene glycol (Mw=1000 g / mol), 1,4-butanediol and β-cyclodextrin are added, and stirred for 24 hours to obtain a mixed solution A;
[0183] (2) Under mechanical stirring, the same volume of 5 wt% Isopar E solution of 1,4-phenylene diisocyanate and 5 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve was 64.5 wt%, the content of the polyol was 16.1 wt%, the content of the cyclodextrin was 3.2 wt%, the content of the chain extender was 5.4 wt%, and the content of the polyisocyanate was 10.8 wt%). After reacting at 50°C for 10 min, heat treatment at 90°C for 30 min obtained a semi-solidified cross-linked product, which was dried and crushed to obtain a lithium adsorption material with a particle size of 2.5 mm.
[0184] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0185] Example 7
[0186] (1) The amino-modified lithium ion sieve A is uniformly dispersed in an aqueous solution by ultrasonication, polyethylene glycol (Mw=1000 g / mol), 1,4-butanediol and β-cyclodextrin are added, and stirred for 24 hours to obtain a mixed solution A;
[0187] (2) Under mechanical stirring, the same volume of 20 wt% Isopar E solution of 1,4-phenylene diisocyanate and 20 wt% 1,3-phenylene diisocyanate was dropped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyol, cyclodextrin, chain extender and polyisocyanate, the content of the amino-modified lithium ion sieve was 12.2 wt%, the content of the polyol was 24.4 wt%, the content of the cyclodextrin was 2.4 wt%, the content of the chain extender was 12.2 wt%, and the content of the polyisocyanate was 48.8 wt%). After reacting at 50°C for 10 min, heat treatment at 80°C for 10 min obtained a semi-solidified cross-linked product, which was dried and crushed to obtain a lithium adsorption material with a particle size of 2.5 mm.
[0188] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0189] The contents of the amino-modified lithium ion sieve, structural unit A, structural unit B, structural unit C and structural unit D of the lithium adsorption material are shown in Table 1. The specific surface area, pore size and pore volume of the lithium adsorption material are shown in Table 2.
[0190] Example 8
[0191] Same as Example 1, except that the β-cyclodextrin in step (1) is replaced by α-cyclodextrin.
[0192] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 75wt%; Ar3 is the residue after dehydroxylation of α-cyclodextrin; and R1 is an alkylene group of C4.
[0193] Example 9
[0194] Same as Example 1, except that the β-cyclodextrin in step (1) is replaced by γ-cyclodextrin.
[0195] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 75wt%; Ar3 is the residue after dehydroxylation of γ-cyclodextrin; and R1 is an alkylene group of C4.
[0196] Example 10
[0197] Same as Example 1, except that the polyethylene glycol (Mw=1000 g / mol) in step (1) was replaced by polyethylene glycol (Mw=2000 g / mol).
[0198] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 75wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0199] Embodiment 11
[0200] The same as in Example 1, except that in step (2), 1,4-phenylene diisocyanate is replaced by m-phenylenediisocyanate, and 1,3-phenylene diisocyanate is replaced by 1,6-hexamethylene diisocyanate.
[0201] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is and -R4- (formula B'), R2 and R3 are both methylene, R4 is a C6 straight-chain alkylene, wherein, based on the total weight of the structural unit C, the content of the structural unit C containing the formula A' is 75wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is a C4 alkylene.
[0202] Example 12
[0203] The same as Example 1, except that the amino-modified lithium ion sieve A in step (1) is replaced by amino-modified lithium ion sieve D.
[0204] In the prepared skeleton, Ar1 is the residue after dehydroxylation of polyethylene glycol; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 75wt%; Ar3 is the residue after dehydroxylation of β-cyclodextrin; and R1 is an alkylene group of C4.
[0205] Comparative Example 1
[0206] The lithium adsorption material was prepared according to the method of Example 1, except that β-cyclodextrin was not added. The performance characteristics of the prepared lithium adsorption material are shown in Tables 1 and 2.
[0207] Comparative Example 2
[0208] The lithium adsorption material was prepared according to the method of Example 1, except that 1,4-butanediol was not added, and the obtained product was soft and had no shape.
[0209] Comparative Example 3
[0210] The lithium adsorption material was prepared according to the method of Example 1, except that polyethylene glycol (Mw=1000 g / mol) was not added in step (1), and the obtained product was broken and had no shape.
[0211] Comparative Example 4
[0212] The lithium adsorption material is prepared according to the method of Example 1, except that the lithium ion sieve in step (1) is an unmodified lithium ion sieve.
[0213] Comparative Example 5
[0214] The reagents are the same as those in Example 1. The lithium ion sieve, polyethylene glycol, diisocyanate and porogen (ammonium bicarbonate) are uniformly mixed with water and granulated to obtain primary particles. The amount of the porogen is 4wt% of the mass of the lithium ion sieve, wherein the molar ratio of the lithium ion sieve, polyethylene glycol and diisocyanate is 100:0.3:0.2, and the particle size of the primary particles obtained by granulation is 0.01mm-0.1mm; the polymerization of diol and diisocyanate is initiated, and the mixture is dried to obtain secondary particles; the secondary particles are mixed with a polyethylene adhesive solution, and the mass mixing ratio of the secondary particles to the polyethylene adhesive (vinylidene chloride and polyvinyl chloride) is 100:9, and secondary granulation is performed to remove the solvent and porogen to obtain lithium adsorption particles.
[0215] Comparative Example 6
[0216] The lithium adsorption material was prepared according to the method of Example 1, except that the amino-modified lithium ion sieve A in step (1) was replaced by modified lithium ion sieve E.
[0217] In the present invention, the contents of amino-modified lithium ion sieve, structural unit A, structural unit B, structural unit C and structural unit D in the lithium adsorption materials prepared in Examples 1-12, Comparative Examples 1-4 and 6 are shown in Table 1. The specific surface area, pore size, pore volume and average particle size of the lithium adsorption materials of Examples 1-12, Comparative Examples 1 and 4-6 are shown in Table 2. The test results of the saturated adsorption capacity, selectivity coefficient, time to reach 90% adsorption capacity, mass loss ratio and adsorption capacity decrease percentage after 30 desorption cycles of the lithium adsorption materials of Examples 1-12, Comparative Examples 1 and 4-6 are shown in Table 3.
[0218] Table 1
[0219]
[0220] Table 2
[0221]
[0222]
[0223] Table 3
[0224]
[0225] It can be seen from the results that the comprehensive performance of the lithium adsorption material obtained by the scheme of the present invention is significantly better than that of comparative examples 1-6. The adsorption time of the lithium adsorption material obtained in Examples 1-12 to reach 90% of the adsorption capacity is less than or equal to 35 minutes, indicating that the lithium adsorption material with sparse bonding of cyclodextrin-polyurethane polymer skeleton has more pores in the middle and strong hydrophilicity, which is more conducive to accelerating the adsorption rate. After 30 cycles of adsorption under alkaline conditions and desorption under acidic conditions, the particle strength and stability of Examples 1-12 remain unchanged, and the mass loss ratio is less than 1%, indicating that the granulated product has a stable structure and good physical and mechanical properties. The lithium adsorption material of Comparative Example 2 is soft and unformed, indicating that the chain extender can give the polyurethane polymer good physical and mechanical properties. The magnesium-lithium selectivity coefficient of the lithium adsorption material of the present invention is greater than or equal to 315, indicating that the lithium adsorption material of the present invention has strong magnesium-lithium selectivity.
[0226] Compared with Comparative Example 1, the skeleton of the lithium adsorption material of the present invention has a cyclodextrin structure, and its selectivity coefficient is higher and the mass loss is smaller. In Comparative Example 3, no polyol is added, and the obtained product is broken and not formed. Comparative Example 4 uses an unmodified lithium ion sieve, and the obtained lithium adsorption material has a material mass loss ratio of 8% after 30 cycles of adsorption under alkaline conditions and desorption under acidic conditions. Comparative Example 5 prepares lithium adsorption particles according to the technical scheme of CN114011386A, and the selectivity and adsorption capacity of its lithium adsorption particles are low. After 30 cycles of adsorption under alkaline conditions and desorption under acidic conditions, the material mass loss is 10%. Comparative Example 6 is modified by mercaptopropyl trimethoxysilane coupling agent, and the modified lithium ion sieve is dispersed in the skeleton of the lithium adsorption material by physical loading. The time of 90% adsorption capacity of the lithium adsorption material is long, the mass loss ratio is high, and the adsorption capacity decreases a lot after 30 desorption cycles.
[0227] Compared with Comparative Examples 1 and 4, the lithium adsorption material of Example 1 has a higher selectivity coefficient and a higher lithium ion adsorption capacity, indicating that cyclodextrin and lithium ion sieve can play a synergistic role, so that the lithium adsorption material has a high lithium ion adsorption capacity in the solution and a strong magnesium-lithium selectivity.
[0228] Figure 1 This is a scanning electron microscope image of the lithium adsorption material of Example 1. It can be seen that the lithium ion sieve is evenly distributed in the skeleton and the material structure is loose. Figure 2 This is a scanning electron microscope image of the lithium adsorption material prepared in Comparative Example 2. It can be seen that the structure of the lithium adsorption material is densely packed and irregular.
[0229] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium adsorption material, characterized in that: The lithium adsorption material includes a skeleton and an amino-modified lithium ion sieve dispersed in the skeleton; The lithium ion sieve is connected to the framework via the structure shown in Formula I; The skeleton includes structural unit A, structural unit B, structural unit C and structural unit D; The structural unit A and the structural unit C are connected by the structure shown in formula II; The structural unit B and the structural unit C are connected by the structure shown in formula III; The structure unit C and the structure unit D form a structure shown in Formula IV; Ar1 is the residue after dehydroxylation of polyol; Ar2 is the residue after dehydroxylation of polyisocyanate; Ar3 is the residue after dehydroxylation of cyclodextrin; R1 is a C3-C6 alkylene group.
2. The lithium adsorption material according to claim 1, wherein The polyol is selected from at least one of polyethylene glycol, polypropylene glycol and polyether polyol, preferably polyethylene glycol; Preferably, the weight average molecular weight of the polyol is 200-2000 g / mol; Preferably, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably β-cyclodextrin; Preferably, Ar2 is selected from at least one of the following groups: Wherein, R2 and R3 are each independently a methylene group, and R4 is a C6-C9 straight chain alkylene group or a branched chain alkylene group.
3. The lithium adsorption material according to claim 1 or 2, based on the total weight of the lithium adsorption material, the content of the amino-modified lithium ion sieve is 38wt%-75wt%, the content of the structural unit A is 10wt%-30wt%, the content of the structural unit B is 3wt%-16wt%, the content of the structural unit C is 6wt%-23wt%, and the content of the structural unit D is 0.3wt%-9wt%; Preferably, based on the total weight of the lithium adsorption material, the content of the amino-modified lithium ion sieve is 45wt%-70wt%, the content of the structural unit A is 13wt%-23wt%, the content of the structural unit B is 6wt%-9wt%, the content of the structural unit C is 8wt%-20wt%, and the content of the structural unit D is 1wt%-7wt%.
4. The lithium adsorption material according to any one of claims 1 to 3, wherein The amino-modified lithium ion sieve is a lithium ion sieve modified by an aminosilane coupling agent; Preferably, based on the total weight of the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is 0.1wt%-2wt%; Preferably, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane; Preferably, the lithium ion sieve is a titanium-based lithium ion sieve, preferably selected from Li2TiO3, Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of; Preferably, the average particle size of the lithium ion sieve is 0.01-500 μm, preferably 0.03-300 μm.
5. The lithium adsorption material according to any one of claims 1 to 4, wherein The specific surface area of the lithium adsorption material is 8-500m 2 / g, preferably 10-30m 2 / g; Preferably, the pore size of the lithium adsorption material is 0.1-10 microns, preferably 2-5 microns; Preferably, the pore volume of the lithium adsorption material is 10-100m 3 / g, preferably 40-60m 3 / g; Preferably, the average particle size of the lithium adsorption material is 0.01-3 mm, preferably 1-3 mm.
6. A method for preparing a lithium adsorption material, characterized in that: The preparation method comprises the following steps: S1, performing amino modification on the lithium ion sieve to obtain an amino-modified lithium ion sieve; S2, mixing the amino-modified lithium ion sieve, the polyol, the cyclodextrin and the chain extender in water to obtain a mixed solution A; S3. Under stirring conditions, an organic solution containing polyisocyanate is added dropwise to mixed solution A to obtain mixed solution B. After the reaction, the product after the reaction is heat-treated to obtain a semi-solidified cross-linked product. After drying and crushing, a lithium adsorption material is obtained.
7. The preparation method according to claim 6, wherein: In step S1, the lithium ion sieve is a titanium-based lithium ion sieve, preferably selected from Li2TiO3, Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of; Preferably, the average particle size of the lithium ion sieve is 0.01-500 μm, preferably 0.03-300 μm; Preferably, the lithium ion sieve is modified by amino silane coupling agent; Preferably, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane; Preferably, the mass ratio of the lithium ion sieve to the aminosilane coupling agent is 1:0.5-2; Preferably, the conditions for the amino modification include: pH value of 1-3, reaction temperature of 40-95° C., and reaction time of 0.5-12 h.
8. The preparation method according to claim 6 or 7, wherein: In step S3, based on the total weight of the amino-modified lithium ion sieve, the polyol, the cyclodextrin, the chain extender and the polyisocyanate, the content of the amino-modified lithium ion sieve is 38wt%-75wt%, the content of the polyol is 10wt%-30wt%, the content of the cyclodextrin is 3wt%-16wt%, the content of the chain extender is 0.3wt%-9wt%, and the content of the polyisocyanate is 6wt%-23wt%; Preferably, based on the total weight of the amino-modified lithium ion sieve, the polyol, the cyclodextrin, the chain extender and the polyisocyanate, the content of the amino-modified lithium ion sieve is 45wt%-70wt%, the content of the polyol is 13wt%-23wt%, the content of the cyclodextrin is 6wt%-9wt%, the content of the chain extender is 1wt%-7wt%, and the content of the polyisocyanate is 8wt%-20wt%; Preferably, the polyol is selected from at least one of polyethylene glycol, polypropylene glycol and polyether polyol, preferably polyethylene glycol; Preferably, the weight average molecular weight of the polyol is 200-2000 g / mol; Preferably, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably β-cyclodextrin; Preferably, the chain extender is 1,4-butanediol and / or 1,3-propylene glycol.
9. The preparation method according to any one of claims 6 to 8, wherein: The polyisocyanate is selected from at least one of m-xylylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,4-phenylene diisocyanate, 1,3-phenylene diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate and trimethylhexamethylene diisocyanate; Preferably, the reaction conditions include: reaction temperature of 30-70°C, preferably 40-60°C; reaction time of 5-100 min, preferably 10-30 min; Preferably, the heat treatment conditions include: heat treatment temperature of 80-150° C., preferably 80-90° C.; heat treatment time of 5-60 min, preferably 10-30 min.
10. The preparation method according to any one of claims 6 to 9, wherein: The preparation method further comprises: eluting the lithium adsorption material with an acidic solution; Preferably, the acidic solution is selected from hydrochloric acid and / or sulfuric acid; Preferably, the concentration of the acidic solution is 0.01-1 mol / L; Preferably, the elution time is 0.5-24h.
11. A lithium adsorption material obtained by the preparation method according to any one of claims 6 to 10.
12. Use of the lithium adsorption material according to any one of claims 1 to 5 and 11 in extracting lithium from salt lakes.
Citation Information
Patent Citations
Resin-based inorganic nanoparticle composite lithium extraction particle
CN111905700A
Preparation method of lithium adsorption particles
CN114011386A
Lithium ion secondary battery
CN115763946A
Current collector for secondary battery and secondary battery using the same
US20120034521A1
Lithium extraction method for alkaline solution
US20240218483A1
Cited By
Preparation method of high-selectivity lithium ion adsorbent
CN121198264A